Progesterone, progestins and the breast in menopause treatment. (4th July 2018) - Gompel, A.; Plu-Bureau, G.
Abstract: Breast cancer is the main risk associated with menopause hormone therapy (MHT). It is a hormone-dependent cancer. In postmenopausal women, about 80% of cases are estradiol receptor-positive. In cohort studies only estradiol receptor-positive breast cancers are promoted by MHT. Different levels of risk with estrogen-only treatment and combined treatment with estrogen + progestin are shown in randomized trials and observational studies. Several non-randomized studies show a lower risk with progesterone and retroprogesterone than with synthetic progestins. Progesterone and progestin are non-selective ligands for the progesterone receptor and bind also with other steroid receptors, with agonistic or antagonistic effects according to the structure of the molecule. Their half-life and metabolism are also different, progesterone being rapidly degraded with a short half-life. These aspects will be discussed in this review.